Aortic valve replacement-induced changes in native T1 are related to prognosis in severe aortic stenosis: T1 mapping cardiac magnetic resonance imaging study. (4th August 2019) - Hwang, In-Chang; Kim, Hyung-Kwan; Park, Jun-Bean; Park, Eun-Ah; Lee, Whal; Lee, Seung-Pyo; Kim, Yong-Jin; Sohn, Dae-Won; Oh, Jae K
Abstract: Aims: Native T1 times from T1 mapping cardiac magnetic resonance (CMR) are associated with myocardial fibrosis in aortic stenosis (AS). We investigated whether changing patterns in native T1 predict clinical outcomes after aortic valve replacement (AVR) in severe AS patients. Methods and results: Forty-three patients with severe AS (65.9 ± 8.1 years; 24 men) who underwent T1 mapping CMR at baseline and 1 year after AVR were prospectively enrolled. Upper limit of native T1 from healthy volunteers was used to define normal myocardium and diffuse fibrosis (native T1 < 1208.4 and ≥1208.4 ms, respectively). Participants were categorized into Group 1 (pre- and post-AVR normal myocardium; n  = 11), Group 2 (pre-AVR diffuse fibrosis and post-AVR normal myocardium; n  = 18), and Group 3 (post-AVR diffuse fibrosis; n  = 14). Native T1 significantly decreased 1 year after AVR (pre-AVR, 1233.8 ± 49.7 ms; post-AVR, 1189.1 ± 58.4 ms; P  < 0.001), which was associated with left ventricular (LV) mass regression (△native T1 vs. △LV mass index, r  = 0.454, P  = 0.010) and systolic function improvement (△native T1 vs. △LV ejection fraction, r  = −0.379, P  = 0.012). Group 2 showed greater functional improvements, whereas these benefits were blunted in Group 3 . Group 3 had significantly worse outcomes than Group 1 [hazard ratio (HR), 9.479, 95% confidence interval (CI) 1.176–76.409; P  = 0.035] and Group 2 (HR 3.551, 95% CI 1.178–10.704; P  = 0.024). Conclusion: AVR-induced changes in native T1 values are associated with LV systolic functional changes as well as prognosis in severe AS. Post-AVR T1 mapping CMR can be used as an imaging biomarker.